Congressos internacionais de Educação Física: produção, debate e circulação de ideias (1900-1913) - Iara Marina dos Anjos Bonifácio (2024)
The International Congresses of Physical Education (CIEP), held between 1900 and 1913 in Europe, are highlighted in the literature as the scene of intense disputes between the different systematisations of physical education. This period is known as the “war of the methods”. These clashes sought to argue and define the best way to exercise and educate the body. The objective of this research was to analyse the production of physical education concepts and practices in the different editions of the International Congress of Physical Education held between 1900 and 1913. The analysis was divided into two axes. The first axis concerns the CIEP as a place for the circulation and debate of ideas. To this end, we investigated the process of proposing and organising it, as well as its effects on the development of physical education in various countries. The second axis of analysis focused on ideas, not only about the method wars, but also about other controversies. The categories of internationalisation, networks, discipline and competent discourse were used in the analyses. As sources, we used the official documents of the Congresses, the publications of the Congress participants, as well as their books and manuals, and physical education magazines and newspapers. Consequently, it can be concluded that the International Congresses of Physical Education constituted a central place for the debate, circulation and production of ideas about physical education that were disseminated across numerous countries worldwide. The Congresses had a significant impact on the formation of an international scientific network and the establishment of two international institutions. Furthermore, it can be posited that at these Congresses, physical education underwent a transformation, moving from being perceived solely as a practice to being regarded and advocated as a discipline, a branch of knowledge. The results of this research, which highlight the dimensions of circulation and exchanges between subjects, contribute to a change in perspective on the processes of constituting physical education as a branch of knowledge. This new view seeks to deconstruct the idea that physical education has been an exclusively national construction and that there are hegemonic centres for the dissemination of ideas. People read, wrote, responded, travelled, carried out scientific experiments, debated at congresses - in other words, they established exchanges that built what we call physical education, even if today this idea still has multiple interpretations around the world.